Preparation method of high-micropore-structure biomass hard carbon negative electrode material of sodium-ion battery

The hard carbon negative electrode material with high microporous structure is prepared through biomass raw materials. The functional group modification and crosslink modification technology are used, combined with high temperature carbonization, and the problems of low specific capacity and excessive mesoporous in the existing technology are solved, achieving the improvement of high sodium storage capacity and Coulomb efficiency, while avoiding equipment corrosion.

CN119528114APending Publication Date: 2025-02-28PUERJIA NA NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765504.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing hard carbon anode material has a lower specific capacity in sodium ion batteries and uses alkaline activators to construct microporous structures, resulting in excessive mesoporous, excessive specific surface area, low first-week efficiency, and serious corrosion of the equipment, affecting actual production.

Method used

Biomass raw materials are used to prepare hard carbon negative electrode materials with high microporous structures, and thermally stable structures are formed through functional group modification and cross-linking modification. Combined with high-temperature carbonization technology, a rich internal pore structure is formed, and alkaline activators are avoided.

Benefits of technology

The sodium storage capacity and Coulomb efficiency of the negative electrode material of sodium ion battery have been significantly improved. The specific surface area of ​​the material does not increase, the efficiency is high in the first week, the process is simple and feasible, and the equipment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528114A_ABST
    Figure CN119528114A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sodium ion battery biomass hard carbon negative electrode material with a high micropore structure. The preparation method comprises the following steps: S1, pretreating raw materials to obtain refined hard carbon raw materials; s2, functional group modification: placing the hard carbon raw material and a modifier in a reaction kettle for temperature control reaction to obtain a modified hard carbon raw material rich in functional groups; s3, cross-linking modification: putting the modified hard carbon raw material and a cross-linking agent into a reaction kettle, and reacting at a controlled temperature to obtain a cross-linked hard carbon raw material; s4, drying treatment: drying the cross-linked hard carbon raw material to obtain a cross-linked hard carbon raw material; s5, pre-carbonization: pre-carbonizing the cross-linked hard carbon raw material in a protective atmosphere to obtain a pre-carbonized material; s6, crushing and refining to obtain a refined pre-carbonized material; and S7, high-temperature carbonization: carrying out high-temperature carbonization on the refined pre-carbonized material in a protective atmosphere to obtain the hard carbon negative electrode material with a high microporous structure. The method has the characteristics of high sodium storage capacity, high coulombic efficiency and high process operability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure. Background Art

[0002] As the core component of sodium-ion batteries, the negative electrode material plays an important role in storing and releasing sodium ions. Its performance directly determines the overall performance of sodium-ion batteries, such as energy density, rate performance and power density.

[0003] Among the negative electrode materials for sodium-ion batteries, the development of hard carbon negative electrode materials is currently limited by their low specific capacity. Hard carbon is an amorphous carbon with no fixed crystal structure and can be considered as a mixed structure consisting of short-range ordered graphite-like microcrystalline regions, amorphous regions and micropores.

[0004] In the preparation method of hard carbon negative electrode materials, pore-forming agents are mainly used to construct microporous structures inside hard carbon materials, increase storage active sites, and increase specific capacity. Commonly used pore-forming agents are generally activators, such as NaOH, KOH, Na2CO3, etc.

[0005] However, this type of activator will also produce a large number of mesopores while constructing micropores inside the hard carbon material. The mesopores do not have sodium storage activity and will make the specific surface area of ​​the hard carbon material too large, resulting in low efficiency in the first week. Therefore, it is necessary to cooperate with the coating process to reduce the specific surface area of ​​the hard carbon material, and the process is complicated. At the same time, NaOH, KOH, Na2CO3 and other substances are extremely alkaline and cause serious corrosion to equipment, which is not conducive to actual production use. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure, which has the characteristics of high sodium storage capacity, high coulombic efficiency and strong process operability.

[0007] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure, comprising the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain refined hard carbon raw materials; S2, functional group modification: wet-mixing the refined hard carbon raw material obtained in step S1 with a modifier to form a first reaction liquid, placing it in a reaction kettle for temperature-controlled reaction, filtering, and centrifuging to obtain a modified hard carbon raw material rich in functional groups; S3, cross-linking modification: wet-mixing the modified hard carbon raw material obtained in step S2 and the cross-linking agent to form a second reaction liquid, placing it in a reaction kettle, reacting under temperature control, filtering, and centrifuging to obtain a cross-linked hard carbon raw material; S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material; S5, pre-carbonization: pre-carbonizing the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material; S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material; S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure.

[0008] Furthermore, in step S2, the amount of modifier added is 0.5-20wt.% of the amount of hard carbon raw material added, the solid content of the reaction solution is 20-35%, the reaction temperature is 60-90°C, and the reaction time is 2-18h. If the amount of modifier added is too little, the reaction temperature is low or the reaction time is insufficient, the purpose of increasing the reaction activity of the precursor cannot be achieved; on the contrary, the polymer in the raw material is easily degraded into low molecular weight compounds, which are dissolved in the solution, resulting in a low yield.

[0009] Further, in step S2, the modifier is one or more of hydrogen peroxide, sodium hypochlorite, potassium hypochlorite, nitric acid, ozone, bromine water, chlorine water, potassium permanganate, and potassium dichromate. The main component of the biomass raw material is a carbon-containing polymer molecule, which is a three-dimensional cross-linked network structure connected by chemical bonds such as CC and CO. The characteristics of its polymer molecular components are low reactivity at room temperature and not easy to undergo chemical cross-linking reactions with other functional groups; but the thermal stability of chemical bonds such as CO at high temperatures is poor, and it is easy to crack at high temperatures, and it is impossible to maintain a stable rigid skeleton structure. During the pyrolysis process, the precursor molecules are cracked at high temperatures to generate volatile gases such as H2O, CO, CO2, and CH4, but because the stable skeleton structure cannot be maintained, the skeleton collapses, so rich internal pores cannot be formed. During the reaction process, the CO bonds in the biomass raw materials are oxidized and digested by the modifier to form functional groups such as -OH or -COOH that are prone to cross-linking reactions.

[0010] Furthermore, in step S3, the amount of crosslinking agent added is 0.5-5wt.% of the amount of modified hard carbon raw material added; the reaction temperature is 50-95°C, and the reaction time is 2-20h. If the amount of crosslinking agent added is too little, the reaction temperature is too low or the reaction time is insufficient, the degree of crosslinking of the active groups of the biomass raw material is insufficient, and the purpose of improving the thermal stability of the carbon material skeleton cannot be achieved; on the contrary, the rigidity of the carbon material skeleton is too strong, the yield of volatile gas is low, and it is not conducive to the formation of a rich microporous structure.

[0011] Furthermore, in step S3, the crosslinking agent is one or more of H2SO4, H2SO3, H3PO4, H3PO2 and their corresponding salts. -OH in the crosslinking agent and the reactive functional groups (-OH and -COOH) formed in the S1 process in the biomass raw material undergo a crosslinking reaction, so that the molecules in the biomass raw material are further polymerized into a skeleton structure with a larger molecular weight. The crosslinked structure formed in this process is a PO bond or a SO bond, which has good thermal stability, so even at a higher pre-carbonization temperature, it can maintain good stability.

[0012] Furthermore, in step S5, the heating rate is 0.5~20℃ / min, the holding temperature is 500~900℃, and the holding time is 2~5h. During the carbonization process, the biomass precursor also contains certain PO bonds or SO bonds, and has good thermal stability, so it can maintain a good rigid structure throughout the carbonization process. On the other hand, there are still a large number of volatile components in the biomass. During the pyrolysis process, the precursor molecules are decomposed at high temperature to generate volatile gases such as H2O, CO, CO2, and CH4. The gases escape into the carbon material skeleton to form a rich pore structure.

[0013] Further, in step S7, the heating rate is 0.5-20°C / min, the temperature is 1000-1500°C, and the time is 1-5 h.

[0014] Furthermore, in step S6, the crushing and refining method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the crushing fineness is 4-12 μm to D50.

[0015] Furthermore, in step S4, the drying temperature is 80-150° C., and the material is dried until the moisture content is ≤5%; in steps S5 and S7, the protective atmosphere is nitrogen and / or argon.

[0016] Further, in step S1, the hard carbon raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, straw, reed, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, bituminous coal, and asphalt; the mesh number of the sieve is ≥ 10 meshes. If the mesh number of the sieve is too small, the raw material particles are too large, and the reagents are not easy to penetrate into the particles, which is not conducive to the occurrence of subsequent modification and cross-linking reactions.

[0017] The present invention provides a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure, which has the following beneficial effects: First, the sodium storage capacity is high. The present invention forms a cross-linked structure with good thermal stability in the precursor skeleton by first modifying and then cross-linking. During the pyrolysis process, the precursor molecules are decomposed at high temperature to generate a large amount of volatile gas. The gas escapes and forms a rich pore structure inside the rigid carbon material skeleton, thereby providing storage space for sodium ions and improving the sodium storage capacity of the negative electrode material of the sodium ion battery. Second, the Coulomb efficiency is high. Compared with the prior art which uses an activator to form pores in the external mesopores that are chemically inactive, the method of the present invention does not use an activator. The rich pores formed are the internal pores of the carbon material rather than the external open pores, which will not increase the specific surface area of ​​the material and will not affect the first-cycle efficiency of the material.

[0018] Third, the process is highly operable. The operating steps of the preparation method of the present invention are all conventional operating steps. The overall preparation route of the hard carbon material with a high microporous structure is formed through the interaction of different steps. The preparation method does not use highly corrosive alkaline substances and does not require additional coating processes. The process is simple and feasible. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The thermogravimetric curves of Application Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0021] The present invention discloses a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure, comprising the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain refined hard carbon raw materials; S2, functional group modification: wet-mixing the refined hard carbon raw material obtained in step S1 with a modifier to form a first reaction liquid, placing it in a reaction kettle for temperature-controlled reaction, filtering, and centrifuging to obtain a modified hard carbon raw material rich in functional groups; S3, cross-linking modification: wet-mixing the modified hard carbon raw material obtained in step S2 and the cross-linking agent to form a second reaction liquid, placing it in a reaction kettle, reacting under temperature control, filtering, and centrifuging to obtain a cross-linked hard carbon raw material; S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material; S5, pre-carbonization: pre-carbonizing the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material; S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material; S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure.

[0022] Furthermore, in step S2, the amount of the modifier added is 0.5-20wt.% of the amount of the hard carbon raw material added, the solid content of the reaction solution is 20-35%; the reaction temperature is 60-90°C, and the reaction time is 2-18h.

[0023] Furthermore, in step S2, the modifier is one or more of hydrogen peroxide, sodium hypochlorite, potassium hypochlorite, nitric acid, ozone, bromine water, chlorine water, potassium permanganate, and potassium dichromate.

[0024] Furthermore, in step S3, the amount of the cross-linking agent added is 0.5-5 wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 50-95°C, and the reaction time is 2-20 hours.

[0025] Further, in step S3, the cross-linking agent is one or more of H2SO4, H2SO3, H3PO4, H3PO2 and their corresponding salts.

[0026] Further, in step S5, the heating rate is 0.5-20°C / min, the insulation temperature is 500-900°C, and the insulation time is 2-5h.

[0027] Further, in step S7, the heating rate is 0.5-20°C / min, the temperature is 1000-1500°C, and the time is 1-5 h.

[0028] Furthermore, in step S6, the crushing and refining method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the crushing fineness is 4-12 μm to D50.

[0029] Furthermore, in step S4, the drying temperature is 80-150° C., and the material is dried until the moisture content is ≤5%; in steps S5 and S7, the protective atmosphere is nitrogen and / or argon.

[0030] Furthermore, in step S1, the hard carbon raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, straw, reed, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, bituminous coal, and asphalt; the mesh size of the sieve is ≥10 meshes.

[0031] Example 1 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Raw material pretreatment: The biomass raw material is crushed and passed through a sieve with a mesh number of ≥10 to obtain a refined hard carbon raw material. Specifically, the hard carbon raw material is coconut shell, walnut shell, nut shell, etc.

[0032] S2, functional group modification: the refined hard carbon raw material obtained in step S1 and the modifier are wet mixed to form a first reaction liquid, which is placed in a reactor for temperature-controlled reaction, filtered, and centrifuged to obtain a modified hard carbon raw material rich in functional groups. Specifically, the amount of the modifier added is 20wt.% of the hard carbon raw material added, the solid content of the reaction liquid is 30%; the reaction temperature is 60°C, the reaction time is 18h, and the modifier is hydrogen peroxide and sodium hypochlorite.

[0033] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2 and the cross-linking agent are wet-mixed to form a second reaction liquid, which is placed in a reactor, reacted under temperature control, filtered, and centrifuged to obtain a cross-linked hard carbon raw material. Specifically, the amount of the cross-linking agent added is 3wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 50°C, the reaction time is 20h, and the cross-linking agent is H2SO4 and its corresponding salts.

[0034] S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material. Specifically, the drying temperature is 120° C., and the material is dried until the moisture content is ≤5%.

[0035] S5, pre-carbonization: pre-carbonize the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the heating rate is 0.5°C / min, the holding temperature is 900°C, the holding time is 3h, and the protective atmosphere is nitrogen.

[0036] S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material. Specifically, the crushing and refining method is jaw crusher and roller crusher, and the crushing fineness is 4-12 μm.

[0037] S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure. Specifically, the heating rate is 0.5°C / min, the temperature is 1500°C, the time is 3h, and the protective atmosphere is nitrogen.

[0038] Example 2 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Raw material pretreatment: The biomass raw material is crushed and passed through a sieve with a mesh number of ≥10 to obtain a refined hard carbon raw material. Specifically, the hard carbon raw material is coconut shell, anthracite, lignite, bituminous coal, and asphalt.

[0039] S2, functional group modification: the refined hard carbon raw material obtained in step S1 and the modifier are wet mixed to form a first reaction liquid, which is placed in a reactor for temperature-controlled reaction, filtered and centrifuged to obtain a modified hard carbon raw material rich in functional groups. Specifically, the amount of the modifier added is 10wt.% of the amount of the hard carbon raw material added, the solid content of the reaction liquid is 20%; the reaction temperature is 90°C, the reaction time is 10h, and the modifiers are potassium permanganate and potassium dichromate.

[0040] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2 and the cross-linking agent are wet-mixed to form a second reaction liquid, which is placed in a reactor, reacted under temperature control, filtered, and centrifuged to obtain a cross-linked hard carbon raw material. Specifically, the amount of the cross-linking agent added is 0.5wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 95°C, the reaction time is 11h, and the cross-linking agent is H2SO3 and its corresponding salts.

[0041] S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material. Specifically, the drying temperature is 80° C., and the material is dried until the moisture content is ≤5%.

[0042] S5, pre-carbonization: pre-carbonize the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the heating rate is 20°C / min, the holding temperature is 700°C, the holding time is 2h, and the protective atmosphere is argon.

[0043] S6, pulverizing and refining: pulverizing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material. Specifically, the pulverizing and refining method is mechanical grinding or Raymond grinding, and the pulverizing fineness is 4-12 μm.

[0044] S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure. Specifically, the heating rate is 20 °C / min, the temperature is 1300 °C, the time is 1 h, and the protective atmosphere is argon.

[0045] Example 3 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the biomass raw material and pass it through a sieve with a mesh number of ≥10 to obtain a refined hard carbon raw material. Specifically, the hard carbon raw material is apricot shell, coffee shell, straw, reed, bamboo, poplar, eucalyptus, pine, fruit wood, etc.

[0046] S2, functional group modification: the refined hard carbon raw material obtained in step S1 and the modifier are wet mixed to form a first reaction liquid, which is placed in a reactor for temperature-controlled reaction, filtered and centrifuged to obtain a modified hard carbon raw material rich in functional groups. Specifically, the amount of the modifier added is 2wt.% of the hard carbon raw material added, the solid content of the reaction liquid is 35%; the reaction temperature is 75°C, the reaction time is 2h, and the modifier is hydrogen peroxide, potassium permanganate, and potassium dichromate.

[0047] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2 and the cross-linking agent are wet-mixed to form a second reaction liquid, which is placed in a reactor, reacted under temperature control, filtered, and centrifuged to obtain a cross-linked hard carbon raw material. Specifically, the amount of the cross-linking agent added is 5wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 75°C, the reaction time is 2h, and the cross-linking agent is H3PO4 and its corresponding salts.

[0048] S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material. Specifically, the drying temperature is 150° C., and the material is dried until the moisture content is ≤5%.

[0049] S5, pre-carbonization: pre-carbonize the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the heating rate is 10°C / min, the holding temperature is 500°C, the holding time is 5h, and the protective atmosphere is nitrogen and argon.

[0050] S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material. Specifically, the crushing and refining method is ball milling, stirring milling, sand milling, and the crushing fineness is 4-12 μm.

[0051] S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure. Specifically, the heating rate is 10°C / min, the temperature is 1000°C, the time is 1-5h, and the protective atmosphere is nitrogen and argon.

[0052] Example 4 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Raw material pretreatment: The biomass raw material is crushed and passed through a sieve with a mesh number of ≥10 to obtain a refined hard carbon raw material. Specifically, the hard carbon raw material is coconut shell, walnut shell, nut shell, apricot shell, coffee shell, etc.

[0053] S2, functional group modification: the refined hard carbon raw material obtained in step S1 and the modifier are wet mixed to form a first reaction liquid, which is placed in a reactor for temperature-controlled reaction, filtered and centrifuged to obtain a modified hard carbon raw material rich in functional groups. Specifically, the amount of the modifier added is 4wt.% of the hard carbon raw material added, the solid content of the reaction liquid is 30%; the reaction temperature is 70°C, the reaction time is 5h, and the modifier is hydrogen peroxide and sodium hypochlorite.

[0054] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2 and the cross-linking agent are wet-mixed to form a second reaction liquid, which is placed in a reactor, reacted under temperature control, filtered, and centrifuged to obtain a cross-linked hard carbon raw material. Specifically, the amount of the cross-linking agent added is 2wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 85°C, the reaction time is 6h, and the cross-linking agent is H3PO2 and its corresponding salt.

[0055] S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material. Specifically, the drying temperature is 100° C., and the material is dried until the moisture content is ≤5%.

[0056] S5, pre-carbonization: pre-carbonize the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the heating rate is 5°C / min, the holding temperature is 600°C, the holding time is 4h, and the protective atmosphere is nitrogen and argon.

[0057] S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material. Specifically, the crushing and refining method is sand grinding, and the crushing fineness is 4-12 μm D50.

[0058] S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure. Specifically, the heating rate is 8°C / min, the temperature is 1100°C, the time is 2h, and the protective atmosphere is nitrogen and argon.

[0059] Example 5 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the biomass raw material and pass it through a sieve with a mesh number of ≥10 to obtain a refined hard carbon raw material. Specifically, the hard carbon raw material is nut shell, apricot shell, coffee shell, straw, reed, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, etc.

[0060] S2, functional group modification: the refined hard carbon raw material obtained in step S1 and the modifier are wet mixed to form a first reaction liquid, which is placed in a reactor for temperature-controlled reaction, filtered, and centrifuged to obtain a modified hard carbon raw material rich in functional groups. Specifically, the amount of the modifier added is 15wt.% of the amount of the hard carbon raw material added, the solid content of the reaction liquid is 25%; the reaction temperature is 80°C, the reaction time is 9h, and the modifiers are potassium hypochlorite, nitric acid, and ozone.

[0061] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2 and the cross-linking agent are wet-mixed to form a second reaction liquid, which is placed in a reactor, reacted under temperature control, filtered, and centrifuged to obtain a cross-linked hard carbon raw material. Specifically, the amount of the cross-linking agent added is 4wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 65°C, the reaction time is 8h, and the cross-linking agent is H2SO4, H3PO4 and their corresponding salts.

[0062] S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material. Specifically, the drying temperature is 110° C., and the material is dried until the moisture content is ≤5%.

[0063] S5, pre-carbonization: pre-carbonize the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material. Specifically, the heating rate is 10°C / min, the holding temperature is 800°C, the holding time is 4h, and the protective atmosphere is nitrogen and argon.

[0064] S6, pulverizing and refining: pulverizing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material. Specifically, the pulverizing and refining method is ball milling, and the pulverizing fineness is 4-12 μm.

[0065] S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure. Specifically, the heating rate is 12°C / min, the temperature is 1400°C, the time is 4h, and the protective atmosphere is nitrogen and argon.

[0066] Application Example 1 This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure, and a preparation method thereof comprises the following steps: S1. Crushing: Crushing the coconut shell raw material and passing it through a 10-mesh sieve to obtain a refined hard carbon raw material.

[0067] S2, modification: The coconut shell raw material of a certain fineness obtained in step S1, hydrogen peroxide and deionized water are placed in a reactor, reacted at 80°C for 5 hours, filtered and centrifuged to obtain a modified hard carbon raw material rich in functional groups. The amount of hydrogen peroxide added is 4.5wt.% of the raw material addition amount, and the solid content of the reaction solution is 26.5%.

[0068] S3, cross-linking modification: the modified hard carbon raw material obtained in step S2, H2SO4 and deionized water are placed in a reaction kettle, reacted at 85°C for 5 hours, filtered and centrifuged to obtain a cross-linked hard carbon raw material, wherein the amount of hydrogen peroxide added is 3.5wt.% of the amount of raw material added.

[0069] S4, drying: drying the cross-linked hard carbon raw material obtained in S3 at 100° C. to obtain a cross-linked hard carbon raw material having a moisture content of 3% after drying.

[0070] S5, pre-carbonization: pre-carbonize the cross-linked hard carbon raw material obtained in step S4 under a nitrogen gas protection atmosphere at a heating rate of 5°C / min, a temperature of 650°C, and a time of 3 hours to obtain a pre-carbonized material.

[0071] S6. Crushing and refining: The pre-carbonized material obtained in step S5 is crushed and refined using a mechanical mill to obtain a pre-carbonized material with a D50 of 7 μm.

[0072] S7, high temperature carbonization: the pre-carbonized material obtained in step S6 is subjected to high temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a temperature of 1400°C, and a time of 3 hours to obtain a high-capacity hard carbon negative electrode material rich in microporous structure.

[0073] Comparative Example 1 (non-oxidation) This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material, and its preparation method comprises the following steps: S1. Crushing: Crushing the coconut shell raw material and passing it through a 10-mesh sieve to obtain a refined hard carbon raw material.

[0074] S2, modification: the coconut shell raw material of a certain fineness obtained in step S1, H2SO4 and deionized water are placed in a reaction kettle, reacted at 85°C for 5 hours, filtered and centrifuged to obtain a cross-linked hard carbon raw material, wherein the amount of hydrogen peroxide added is 3.5wt.% of the amount of raw material added.

[0075] S3, drying: drying the cross-linked hard carbon raw material obtained in S2 at 100° C. to obtain a cross-linked hard carbon raw material having a moisture content of 3% after drying.

[0076] S4, pre-carbonization: the cross-linked hard carbon raw material obtained in step S3 is pre-carbonized under a nitrogen gas protection atmosphere at a heating rate of 5°C / min, a temperature of 650°C, and a time of 3 hours to obtain a pre-carbonized material.

[0077] S5. Crushing and refining: The pre-carbonized material obtained in step S4 is crushed and refined using a mechanical mill to obtain a pre-carbonized material with a D50 of 7 μm.

[0078] S6. High-temperature carbonization: The pre-carbonized material obtained in step S5 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a temperature of 1400°C, and a time of 3 hours to obtain the hard carbon negative electrode material of comparative example 1.

[0079] Comparative Example 2 (No cross-linking) This embodiment relates to a sodium ion battery biomass hard carbon negative electrode material, and its preparation method comprises the following steps: S1. Crushing: Crushing the coconut shell raw material and passing it through a 10-mesh sieve to obtain a refined hard carbon raw material.

[0080] S2, modification: The coconut shell raw material of a certain fineness obtained in step S1, hydrogen peroxide and deionized water are placed in a reactor, reacted at 80°C for 5 hours, filtered and centrifuged to obtain a modified hard carbon raw material rich in functional groups. The amount of hydrogen peroxide added is 4.5wt.% of the raw material addition amount, and the solid content of the reaction solution is 26.5%.

[0081] S3, drying: drying the modified hard carbon raw material obtained in S2 at 100° C. to obtain a modified hard carbon raw material with a moisture content of 3% after drying.

[0082] S4, pre-carbonization: the modified hard carbon raw material obtained in step S3 is pre-carbonized under a nitrogen gas protection atmosphere at a heating rate of 5°C / min, a temperature of 650°C, and a time of 3 hours to obtain a pre-carbonized material.

[0083] S5. Crushing and refining: The pre-carbonized material obtained in step S4 is crushed and refined using a mechanical mill to obtain a pre-carbonized material with a D50 of 7 μm.

[0084] S6. High-temperature carbonization: The pre-carbonized material obtained in step S5 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a temperature of 1400°C, and a time of 3 hours to obtain the hard carbon negative electrode material of comparative example 2.

[0085] The application example 1, the comparative example 1 and the comparative example 2 were subjected to comparative tests, and the test items and results are as follows: The specific surface areas of Example 1, Comparative Example 1 and Comparative Example 2 were measured by nitrogen adsorption and desorption test to be 4.8, 5.9 and 5.4 m 2 / g, all have a small specific surface area.

[0086] The true density of Example 1, Comparative Example 1 and Comparative Example 2 was measured by true density test to be 1.85, 1.96 and 2.01 g / m 3 , indicating that modification followed by cross-linking can significantly increase the micropore content inside the hard carbon material, thereby reducing the true density of the hard carbon material.

[0087] Through thermogravimetric testing, it can be found that Figure 1The thermogravimetric curves of Application Example 1 and Comparative Example 1 show that the decomposition temperature of Application Example 1 is relatively high, the thermal stability is higher, and the final yield is higher.

[0088] The first-week charging specific capacities of Example 1, Example 2 and Comparative Example 1 measured by constant current charge and discharge tests were 338, 296 and 282 mAh / g, respectively, indicating that the rich microporous structure inside the hard carbon material can effectively improve its sodium storage capacity.

[0089] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure, characterized in that The following steps are involved: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain refined hard carbon raw materials; S2, functional group modification: wet-mixing the refined hard carbon raw material obtained in step S1 with a modifier to form a first reaction liquid, placing it in a reaction kettle for temperature-controlled reaction, filtering, and centrifuging to obtain a modified hard carbon raw material rich in functional groups; S3, cross-linking modification: wet-mixing the modified hard carbon raw material obtained in step S2 and the cross-linking agent to form a second reaction liquid, placing it in a reaction kettle, reacting under temperature control, filtering, and centrifuging to obtain a cross-linked hard carbon raw material; S4, drying treatment: drying the cross-linked hard carbon raw material obtained in S3 to obtain a dried cross-linked hard carbon raw material; S5, pre-carbonization: pre-carbonizing the dried cross-linked hard carbon raw material obtained in step S4 under a protective atmosphere to obtain a pre-carbonized material; S6, crushing and refining: crushing and refining the pre-carbonized material obtained in step S5 to obtain a refined pre-carbonized material; S7, high temperature carbonization: the refined pre-carbonized material obtained in step S6 is subjected to high temperature carbonization under a protective atmosphere to obtain a hard carbon negative electrode material with a high microporous structure.

2. The method for preparing a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure according to claim 1, characterized in that: In step S2, the amount of the modifier added is 0.5-20wt.% of the amount of the hard carbon raw material added, the solid content of the reaction solution is 20-35%; the reaction temperature is 60-90°C, and the reaction time is 2-18h.

3. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 1, characterized in that: In step S2, the modifier is one or more of hydrogen peroxide, sodium hypochlorite, potassium hypochlorite, nitric acid, ozone, bromine water, chlorine water, potassium permanganate, and potassium dichromate.

4. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 1, characterized in that: In step S3, the amount of the cross-linking agent added is 0.5-5 wt.% of the amount of the modified hard carbon raw material added; the reaction temperature is 50-95°C, and the reaction time is 2-20 hours.

5. The method for preparing a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure according to claim 1, characterized in that: In step S3, the cross-linking agent is one or more of H2SO4, H2SO3, H3PO4, H3PO2 and their corresponding salts.

6. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 1, characterized in that: In step S5, the heating rate is 0.5-20°C / min, the holding temperature is 500-900°C, and the holding time is 2-5h.

7. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 1, characterized in that: In step S7, the heating rate is 0.5-20°C / min, the temperature is 1000-1500°C, and the time is 1-5h.

8. The method for preparing a sodium ion battery biomass hard carbon negative electrode material with a high microporous structure according to claim 1, characterized in that: In step S6, the grinding and refining method is one or more of jaw crusher, roller mill, mechanical mill, Raymond mill, air flow mill, ball mill, stirred mill and sand mill, and the grinding fineness is 4-12 μm.

9. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 1, characterized in that: In step S4, the drying temperature is 80-150° C., and the material is dried until the moisture content is ≤5%. In steps S5 and S7, the protective atmosphere is nitrogen and / or argon.

10. The method for preparing a biomass hard carbon negative electrode material for a sodium ion battery with a high microporous structure according to claim 9, characterized in that: In step S1, the hard carbon raw material is one or more of coconut shell, walnut shell, nut shell, apricot shell, coffee shell, straw, reed, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, bituminous coal, and asphalt; the mesh size of the sieve is ≥10 meshes.